Impaired vascular-mediated clearance of brain amyloid beta in Alzheimer’s disease: The role, regulation and restoration of LRP1 - Ramanathan, Anita; Nelson, Amy R.; Sagare, Abhay P.; Zlokovic, Berislav V. (Frontiers in Aging Neuroscience, 2015)
Amyloid beta (Aβ) homeostasis in the brain is governed by its production and clearance mechanisms. An imbalance in this homeostasis results in pathological accumulations of cerebral Aβ, a characteristic of Alzheimer’s disease (AD). While Aβ may be cleared by several physiological mechanisms, a major route of Aβ clearance is the vascular-mediated removal of Aβ from the brain across the blood-brain barrier (BBB). Here, we discuss the role of the predominant Aβ clearance protein – low-density lipoprotein receptor-related protein 1 (LRP1) – in the efflux of Aβ from the brain. We also outline the multiple factors that influence the function of LRP1-mediated Aβ clearance, such as its expression, shedding, structural modification and transcriptional regulation by other genes. Finally, we summarize approaches aimed at restoring LRP1-mediated Aβ clearance from the brain.